Defending in 4-4-2 or 5-3-2 formation? small differences in footballers` collective tactical behaviours - Low, B.; Rein, R.; Schwab, S.; Memmert, D. (Journal of Sports Sciences, 2022)
This study explored footballers` tactical behaviours, based on their position data, as an effect of two defending formations, 4-4-2 and 5-3-2, using an experimental approach. Sixty-nine youth footballers participated in this 11-versus-11 study, performing 72 trials of attack-versus-defence. Players` position data were tracked using a local positioning system, and processed to calculate measures of collective movement. This was supplemented by the analysis of passing networks. The results showed small differences between the two conditions. Compared to a 4-4-2 formation, defending in 5-3-2 reduced dispersion (-0.69 m,p=0.012), midfield-forward distance (-0.81 m, p=0.047), and defence-forward distance (-1.29 m, p=0.038); the consequent effects on attacking teams included reduced team widths (-1.78 m, p=0.034), reduced necessity for back-passes to the goalkeeper, and less connectivity in the passing network. The effects of the two defending formations seem to have the greatest impact on fullbacks of the attacking teams, since they were main contributors of the reduced team widths, received more passes, and had higher betweenness centrality in the right-back position during 5-3-2 defending. In summary, the present study potentially demonstrates how the underlying mechanisms in players` collective movements and passing behaviours show that the 5-3-2 is more conservatively defensive than the 4-4-2.